Health Information Seeking as a Cognitive Coping Mechanism in Stunting Prevention among Mothers - Besar Tirto Husodo; Bagoes Widjanarko; Bulan Prabawani; Hari Susanta Nugraha (Universitas Ahmad Dahlan, 2026)
Stunting remains a persistent public health concern in urban Semarang, Central Java; however, mothers’ coping processes are still weakly operationalized in prior research. While the Theory of Reasoned Action (TRA) offers a useful lens for understanding how people make health-related decisions, it is better understood as a social–cognitive decision-making framework than a full coping model, and the real-world links between seeking health information, responding to it, and taking action to prevent stunting have rarely been put to the test. This study set out to explore how maternal health information seeking, viewed here as a form of cognitive coping, relates to stunting prevention practices, drawing on the TRA to understand how gathering information might lead mothers to take deliberate preventive steps. A cross-sectional survey was administered to 337 mothers from Central Java, Indonesia. Structured questionnaires were used to assess health information-seeking behavior, social media utilization, family health communication, and stunting prevention practices. Data were analyzed using descriptive statistics and chi-square tests. Most mothers reported moderate to high information-seeking (51.6% moderate; 46.9% high) and high prevention practices (66.2%). Information seeking was strongly associated with stunting prevention practices (χ² = 98.612, df = 4, p < .001). Social media use was also significantly related to information seeking (χ² = 116.428, df = 4, p < .001). In addition, 73.9% received information related to stunting during pregnancy, and 90.2% reported intensive family health communication. These findings suggest that health information seeking functions as an effective cognitive coping mechanism that shapes maternal stunting prevention behaviors. Digital health interventions leveraging social media and strengthening family communication may enhance maternal coping and improve prevention outcomes in the future.